2020
DOI: 10.5194/amt-13-1467-2020
|View full text |Cite
|
Sign up to set email alerts
|

Testing the near-field Gaussian plume inversion flux quantification technique using unmanned aerial vehicle sampling

Abstract: Abstract. Methane emission fluxes from many facility-scale sources may be poorly quantified, potentially leading to uncertainties in the global methane budget. Accurate atmospheric measurement-based flux quantification is urgently required to address this. This paper describes the first test (using unbiased sampling) of a near-field Gaussian plume inversion (NGI) technique, suitable for facility-scale flux quantification, using a controlled release of methane gas. Two unmanned-aerial-vehicle (UAV) platforms we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…This method requires adequate spatial sampling density in both the y and z directions to resolve a flux [66]. Shah et al [38] tested the NGI method using controlled releases of methane. Two rotary-wing UAVs were used: one tethered to a ground-based off-axis ICOS instrument (Los Gatos Research (now ABB) Micro-portable Greenhouse Gas Analyzer), and the second carrying a miniaturized, lighter prototype of the same instrument.…”
Section: (B) Gaussian Plume Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method requires adequate spatial sampling density in both the y and z directions to resolve a flux [66]. Shah et al [38] tested the NGI method using controlled releases of methane. Two rotary-wing UAVs were used: one tethered to a ground-based off-axis ICOS instrument (Los Gatos Research (now ABB) Micro-portable Greenhouse Gas Analyzer), and the second carrying a miniaturized, lighter prototype of the same instrument.…”
Section: (B) Gaussian Plume Inversionmentioning
confidence: 99%
“…The reported lower (17 ± 10%) and upper (227 ± 98%) uncertainty bounds resulted from the variability in the position of instantaneously observed plumes and spatially sparse sampling. While these uncertainties are large, Shah et al [38] concluded that the NGI method is viable in situations where access to an emission source site is prohibited or impractical.…”
Section: (B) Gaussian Plume Inversionmentioning
confidence: 99%
“…It was noted in both Allen et al 25 and Villa et al 27 that there were no fast high precision CH 4 instruments (defined as better than 100 and 40 ppb/s at 1σ, respectively) available for small UAVs (<7 kg) on the market but that this was a possible future improvement and that simultaneous wind measurements ideally should be made using an instrument on the UAV. Shah et al 28 used two UAVs to measure a controlled CH 4 release: one with an on-board anemometer and a ground-based near-IR CH 4 analyzer connected via tubing and the other UAV with an on-board near-IR CH 4 analyzer (ABB-pMGGA, 3.4 kg and 2.2 ppb precision at 1 Hz). In this paper, we present a small, customized rotary UAV system (6.7 kg total weight; flight time 10 min per battery pair) with the capability to directly map CH 4 hotspots and to measure total area fluxes using on-board instrumentation only, including wind and CH 4 concentrations at high precision and frequency (0.84 ppb and 0.1 m/s at 1 Hz) using a lightweight mid-IR CH 4 sensor (Aeris MIRA Pico, 1.9 kg).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new measurement systems and technologies have been developed to quantify emissions of methane from equipment and operations with reduced cost and/or improved spatial coverage. Examples include portable methane analyzers [5], open-path laser spectrometers [6], remote sensing of methane from aircraft and satellite [7][8][9], groundbased mobile sensing [10,11] , and airborne mobile sensing approaches using unmanned aerial vehicles (UAVs) [12][13][14][15]. Use of portable methane analyzers is an accurate method for quantifying known emission sources, but localization efforts are often labor intensive with the requirement of investigating entire facilities at a slow pace.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based mobile sensing approaches are useful in quantifying emissions from facilities without offering solutions for component leak localization [16,17]. While the use of UAV systems has been promising for leak detection, localization and quantification, large uncertainties arise from the reliance on lightweight sensors and simplistic dispersion models [12,14]. It is worth noting that many non-invasive approaches including transient test-based techniques (TTBTs) have shown success in leak detection and quantification in water systems [18][19][20].…”
Section: Introductionmentioning
confidence: 99%